Densifying hydration products of alite by a bio-inspired admixture - Yi Fang; Jialai Wang; Liang Wang; Xin Qian; Xiaodong Wang; Wenyu Liao; Peiyuan Chen; Hongyan Ma (Materials & Design, 2023)
A bio-inspired, plant-derived polyphenol, tannic acid (TA) was identified as a renewable admixture to improve the compressive strength of concretes. Aiming to understand the underlying mechanism responsible for this strength improvement, this study examines how TA mediates the hydration of tricalcium silicate (alite). Experimental study shows that TA can form complex with calcium ions through chelating, retarding the hydration of the alite and changing of the hydration products. Particularly, X-ray diffraction analysis shows that TA makes calcium hydroxide preferentially grow on the [001] face. Fourier-transform infrared spectroscopy and 29Si MAS NMR results reveal that the mean chain length of calcium silicate hydrate (CSH) is reduced by TA. More importantly, mercury intrusion porosimetry testing reveals that pores with size near 30 nm was almost eliminated by adding TA, leading to higher elastic modulus of the produced CSH and higher compressive strength of the produced concrete.